Application of 7-azaisatins in enantioselective Morita–Baylis–Hillman reaction - He, Qing; Zhan, Gu; Du, Wei; Chen, Ying-Chun (Beilstein Journal of Organic Chemistry, 2016)
7-Azaisatin and 7-azaoxindole skeletons are valuable building blocks in diverse biologically active substances. Here 7-azaisatins turned out to be more efficient electrophiles than the analogous isatins in the enantioselective Morita–Baylis–Hillman (MBH) reactions with maleimides using a bifunctional tertiary amine, β-isocupreidine (β-ICD), as the catalyst. This route allows a convenient approach to access multifunctional 3-hydroxy-7-aza-2-oxindoles with high enantiopurity (up to 94% ee). Other types of activated alkenes, such as acrylates and acrolein, could also be efficiently utilized.
Keywords: 7-azaisatins; β-isocupreidine; bifunctional catalysis; maleimide; MBH reaction

(untitled) - Basavaiah, D.; Rao, K. V.; Reddy, R. J. (Chem. Soc. Rev., 2007)

(untitled) - Basavaiah, D.; Reddy, B. S.; Badsara, S. S. (Chem. Rev., 2010)

(untitled) - Cran, J. W.; Krafft, M. E.; Seibert, K. A.; Haxell, T. F. N.; Wright, J. A.; Hirosawa, C.; Abboud, K. A. (Tetrahedron, 2011)

(untitled) - Wei, Y.; Shi, M. (Chem. Rev., 2013)

(untitled) - Liu, Y.-L.; Wang, B.-L.; Cao, J.-J.; Chen, L.; Zhang, Y.-X.; Wang, C.; Zhou, J. (J. Am. Chem. Soc., 2010)

(untitled) - Guan, X.-Y.; Wei, Y.; Shi, M. (Chem. – Eur. J., 2010)

(untitled) - Qian, J.-Y.; Wang, C.-C.; Sha, F.; Wu, X.-Y. (RSC Adv., 2012)

(untitled) - Duan, Z.; Zhang, Z.; Qian, P.; Han, J.; Pan, Y. (RSC Adv., 2013)

(untitled) - Dong, Z.; Yan, C.; Gao, Y.; Dong, C.; Qiu, G.; Zhou, H.-B. (Adv. Synth. Catal., 2015)

(untitled) - Zhao, X.; Li, T.-Z.; Qian, J.-Y.; Sha, F.; Wu, X.-Y. (Org. Biomol. Chem., 2014)

(untitled) - Zhong, F.; Chen, G.-Y.; Lu, Y. (Org. Lett., 2011)

(untitled) - Yoshida, Y.; Sako, M.; Kishi, K.; Sasai, H.; Hatakeyama, S.; Takizawa, S. (Org. Biomol. Chem., 2015)

(untitled) - Chauhan, P.; Chimni, S. S. (Asian J. Org. Chem., 2013)

(untitled) - Kumar, A.; Sharma, V.; Kaur, J.; Kumar, N.; Chimni, S. S. (Org. Biomol. Chem., 2015)

(untitled) - Wood, E. R.; Kuyper, L.; Petrov, K. G.; Hunter, R. N., III; Harris, P. A.; Lackey, K. (Bioorg. Med. Chem. Lett., 2004)

(untitled) - Kritsanida, M.; Magiatis, P.; Skaltsounis, A.-L.; Peng, Y.; Li, P.; Wennogle, L. P. (J. Nat. Prod., 2009)

(untitled) - Rekulapally, S.; Jarapula, R.; Gangarapu, K.; Manda, S.; Vaidya, J. R. (Med. Chem. Res., 2015)

(untitled) - Liu, Y.-L.; Wang, X.; Zhao, Y.-L.; Zhu, F.; Zeng, X.-P.; Chen, L.; Wang, C.-H.; Zhao, X.-L.; Zhou, J. (Angew. Chem., 2013)

(untitled) - Yin, X.-P.; Zeng, X.-P.; Liu, Y.-L.; Liao, F.-M.; Yu, J.-S.; Zhou, F.; Zhou, J. (Angew. Chem., Int. Ed., 2014)

(untitled) - Peng, J.; Huang, X.; Cui, H.-L.; Chen, Y.-C. (Org. Lett., 2010)

(untitled) - Peng, J.; Huang, X.; Jiang, L.; Cui, H.-L.; Chen, Y.-C. (Org. Lett., 2011)

(untitled) - Peng, J.; Huang, X.; Zheng, P.-F.; Chen, Y.-C. (Org. Lett., 2013)

(untitled) - Peng, J.; Ran, G.-Y.; Du, W.; Chen, Y.-C. (Org. Lett., 2015)

(untitled) - Nakamoto, Y.; Urabe, F.; Takahashi, K.; Ishihara, J.; Hatakeyama, S. (Chem. – Eur. J., 2013)

(untitled) - Peng, J.; Ran, G.-Y.; Du, W.; Chen, Y.-C. (Synthesis, 2015)